Optimizing Assessment for Learning in Islamic Education through Authentic and Diagnostic Assessment : A Systematic Literature Review - Nilna Fadlillah; Kusaeri Kusaeri (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to provide a comprehensive overview of research trends in authentic and diagnostic assessments, analyze the factors that influence their implementation and effectiveness, and the potential for optimizing both assessments to improve the quality of Islamic learning. Using the Systematic Literature Review method with Watase Uake and Publish or Perish tools, this study screened 825 articles according to PRISMA guidelines. After identifying, screening, and eligibility, 46 articles Scopus Indexed, Sinta 1, and Sinta 2 were selected for further mapping and thematic analysis. The results showed that 1) the main trends of the research were related to the integration of technology in both assessments through e-portfolios and eDia System; 2) factors affecting effectiveness included validity and reliability of instruments, simplification of trials and validation, and integration of technology, while the obstacles were dominated by the lack of understanding of teachers, the complexity of procedures, and limited resources and time; 3) optimization steps included comprehensive training for teachers, development and validation of instruments, provision of supporting facilities, as well as the need for technology integration to make Islamic learning more dynamic, efficient, holistic, and meaningful. This study can be a reference for educators and education managers to improve assessment practices in learning Islamic Religion so that it can effectively achieve the goals of holistic Islamic education.